The floor of heaven : a true tale of the last frontier and the Yukon gold rush - Blum, Howard (New York : Crown Publishers, 2011)
Using primary source materials from three individuals around whom the narrative revolves, best-selling author Blum tells a story of the 1897 Klondike Gold Rush.
Traces the experiences of 1890s prospector-turned-tycoon George Carmack, cowboy detective Charlie Siringo, and con man Soapy Smith to reveal how the opening of the "last frontier" in Alaska shaped America's national character.
Includes bibliographical references (p. 408-418).
Keywords: Siringo, Charles A., -- 1855-1928; Smith, Jefferson Randolph, -- 1860-1898.; Carmack, George W. -- 1860-1922.; Siringo, Charles A., -- 1855-1928; Smith, Jefferson Randolph, -- 1860-1898.; Carmack, George W. -- 1860-1922.; Gold mines and mining -- History -- Yukon River Valley (Yukon and Alaska) -- 19th century; Gold mines and mining -- Yukon River Valley (Yukon and Alaska) -- History; Yukon River Valley (Yukon and Alaska) -- Gold discoveries; West (U.S.) -- History -- 1860-1890.; Yukon River Valley (Yukon and Alaska) -- Biography; West (U.S.) -- Biography; Yukon River Valley (Yukon and Alaska) -- Gold discoveries; West (U.S.) -- History -- 19th century; Yukon River Valley (Yukon and Alaska) -- Biography; West (U.S.) -- Biography; Biographies